DNA-based computing - Yong, Kian Yan (2013)
DNA-based computing provides an alternative to solving optimization problems in graph theory. In this research, it is shown how DNA-based computing is used to find solutions to these problems, which involve logical thinking and are often NP hard complete. These include the shortest path, shortest spanning tree, maximum flow and maximum bipartite matching problems. DNA-based computing is a suitable tool for these problems because of its massive parallelism during computation. The success of a DNA-based experiment designed around the shortest path problem, global positioning system problem, reinforced and revealed the potential of this approach.